On the Semiotic Interpretation of the Epic Poems “David of Sassoon” and “Beowulf” - Matevosyan, Armine; Mardoyan, Liza (Armenian Folia Anglistika, 2013)
The article considers the semiotic features underlying in epic poems David of Sassoon and Beowulf. An attempt has been made to examine linguistic and extra-linguistic semiotic units (sign-word; sign-symbol, sign-expression) that are of central importance to the poems mentioned.